INXU: A Flow-Based Intrusion Prevention System for Home IoT Networks - Morais, Sávyo V.; Farias, Claudio M. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais Estendidos do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg_estendido.2022.224947, 2022)
Due to the low resources and maintainability in home Internet of Things (IoT) devices, they can represent a risk to end-user’s security and privacy. Several proposals tried to manage new vulnerabilities in this scenario, but it is difficult to keep signatures updated or identify anomalous traffic. To reinforce home IoT security, we propose INXU, a flow-based Intrusion Prevention System that protects home IoT devices by blocking traffic related to well known malicious activities. INXU introduces the concept of Malicious Traffic Description (MTD), a data-model to describe traffic related to malicious activities that enables Security Experts to protect home networks and keeps end-user’s privacy. Experiments using Mirai botnet have shown the efficacy of our solution.